KEJAHATAN PROSTITUSI ONLINE DI KOTA PONTIANAK DALAM TEORI ASOSIASI DIFERENSIAL - NIM. A1011201239, NUR HAIDIR (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractThe state of online prostitution in the city of Pontianak, as in many other cities in Indonesia, reflects a pattern similar to national trends. Although there is no precise data regarding the number of online prostitution perpetrators in Pontianak, this practice can be found through the digital social media platform, namely MiChat. The problem in this research is: